PKM Sosialisasi Integrasi Solidaritas Dalam Organisasi Kemahasiswaan - Yusuarsono, Yusuarsono; Lorita, Evi; Sariningsih, Marida; Saputra, Harius Eko; Rikardo, Yanuar; Sahara, Sherly Marta (Jurnal Dehasen Untuk Negeri, 2024)
This Community Service (PKM) activity aims to foster and strengthen the value of social solidarity in student organizations, especially the Public Administration Student Association (HIMAPLIK) of Dehasen University, Bengkulu. In the era of globalization that is full of challenges of individualism and rapid social change, the millennial generation as part of the academic community needs to have a high collective awareness and spirit of togetherness to maintain the integrity of the organization. This activity was carried out in the form of a Public Dialogue with the theme "Integration of Solidarity in Student Organizations", which was attended by HIMAPLIK administrators and members. The activity method used a participatory approach through lectures, interactive discussions, and question and answer sessions to increase participants' understanding of the meaning, forms, and application of positive social solidarity in organizations. The results of the activity showed that HIMAPLIK students have an awareness of the importance of solidarity in maintaining cohesiveness, cooperation, and shared responsibility. Social solidarity is interpreted as a form of togetherness, sincerity, mutual cooperation, and mutual support in achieving organizational goals. This activity also encourages students to be more active, communicative, and play a role in building a harmonious and productive organizational climate. Through this PKM activity, it is hoped that HIMAPLIK can become a forum for forming the character of students who are socially minded, disciplined, and oriented towards the values ​​of togetherness in academic and social life.